Simulasi efek peningkatan wisman Cina terhadap perekonomian Sulawesi Utara - Fevriera, Sotya; Hanafi, Rifki Ega (Journal of Economics Research and Policy Studies, 2025)
The Ministry of Tourism and Creative Economy (Kemenparekraf) tries to recover the tourism sector after the pandemic by speeding up the development of five super-priority tourism destinations, one of which is Likupang di North Sulawesi. The Governor set a target of 1 million foreign tourists from China. However, this cannot be achieved in one year. This study aims to simulate the effect of an increase in tourists from China on output, gross value added (GVA), and labor absorption in North Sulawesi. Besides that, this study also seeks to identify relationships among production sectors in North Sulawesi. This study employs input-output analysis with a 2016 input-output table. The study identifies four key sectors: energy and waste, transportation and warehousing, industry, and communications. The sector projected to experience the most significant increase in total output, GVA, and employment is the hotel and restaurant sector. Four other sectors are expected to show significant increases in output and GVA: trade, agriculture, transportation and warehousing, and other services. Meanwhile, the three sectors projected to experience the most significant increase in employment are trade, agriculture, and other services.